Mengembangkan Kompetensi Sumber Daya Manusia Penyelenggara Kesejahteraan Sosial di Daerah Improving Human Resources Competencies Of Social Welfare Area Organizers - Rusmiyati, Chatarina; Hikmawati, Eny (Jurnal Penelitian Kesejahteraan Sosial, 2019)
abstract The Human Resources of Social Welfare Organizer act as executing performers, drivers or companions of social activity programs. This study was aimed to know the Human Resources Competencies of Social Welfare Area Organizers and the effort to improve the competencies concerned. It was a qualitative descriptive research to describe the current competencies of social welfare area organizers and the effort to improve those competencies. The location of the research was determined purposively and it was in Banjarmasin City. This city was chosen because there was a social home managed by the local government namely LKS PSBW Melati and that of LKSA Hikmah Zam Zam managed by a private party. The data was collected and analyzed descriptively to explain the Human Resources Competencies in organizing social welfare for local area. The result of the research showed that from the view point of education aspect, the majority of the human resources concerned graduated from universities but they had not had any educational background of being social workers. The ratio of the amount of the human resources and the clients served had not been in accordance with the LKS organization guidances yet. The quality of the service was influenced by the human resources concerned length of work, the longer the length of work was, the more experiences related to the duties and responsibilities they would have accordingly. The social service process in LKS had met the standard procedures appropriately covering the service stage to termination. The human resources competency and capacity of social welfare organizers need to be developed by attending social work training and practicing so that they are able to carry out social service on the base of social works. Â Key Words: competency; human resources; social welfare organizer